Penentuan Alternatif Lokasi Gudang Akhir Rumput Laut Dengan Metode Center of Gravity dan Point Rating (Studi Kasus Di Kabupaten Seram Bagian Barat) - D. B. Paillin; Melkias Thony Dasfordate (ARIKA, 2012)
Warehouse is the basic of national logistic strategy. This research aims to determine an optimal location of an seaweed- end warehouse. We use two methods, Center of Gravity and metode Point Rating, which is aplicated to Analitical Hierarchy Process method with Rating Liberatore scale. This research arranges to select 3 potential location: Dusun Airpessy, Dusun Wael, and Dusun Kotania. Calculation results of those methods recomandate a same optimal location, Dusun Airpessy.